2020
DOI: 10.1097/inf.0000000000002769
|View full text |Cite
|
Sign up to set email alerts
|

Orchiepididymitis in a Boy With COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) symptoms in children are incompletely described. We present the first case of orchiepididymitis associated with COVID-19 in a boy and discuss pathways of testicular involvement by SARS-CoV2 virus. This case underlines the need for further study of the clinical presentation of pediatric COVID-19 and the potential association with nonrespiratory symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 5 publications
3
60
0
Order By: Relevance
“…The third one was a lethal case in a 43-year-old man [45]. Another case was a diagnosis of orchi-epididymitis in a 14-year-old boy with concurrent COVID-19 infection [46].…”
Section: Covid-19 and Gonadal Pathologymentioning
confidence: 99%
“…The third one was a lethal case in a 43-year-old man [45]. Another case was a diagnosis of orchi-epididymitis in a 14-year-old boy with concurrent COVID-19 infection [46].…”
Section: Covid-19 and Gonadal Pathologymentioning
confidence: 99%
“…The relationship between testicular pain and COVID‐19 is one of the least informed subjects among the existing urological diseases. In the current literature, only one case report was published regarding COVID‐19‐related scrotal or testicular pain 15,16 . In this study, we aimed to evaluate COVID‐19‐related testicular pain in hospitalised patients because of COVID‐19 and to review as an aetiological factor for epididymo‐orchitis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a previous study has shown that testicular damage, orchitis and sterility are possible complications of SARS-CoV (Xu et al, 2006). Recently, a case report study showed that orchiepididymitis in a 14-year-old boy seemed to be a complication of COVID-19 (Gagliardi et al, 2020). Notably, higher expression of ACE2 in male gonads seems to be associated with younger age and, as a result, provides evidence that younger patients are more vulnerable to gonadal involvement by SARS-CoV-2 (Shen et al, 2020).…”
mentioning
confidence: 99%